Preface to the December 2014 issue - Héctor Cancela (CLEI Electronic Journal, 2014)
Since 1998, CLEIej has been the leading electronic, open access journal in Computer Science in Latin America. This pioneering role has enabled the regional community to take advantage from a high-quality, peer-reviewed venue for publishing original research in all areas related to computing.